(untitled) (Texas Journal of Engineering and Technology, 2023)
Green building is regarded as a significant component of achieving sustainability because they rely on green and natural elements that reduce pollution and aim to reduce resource consumption. This paper research is concerned with defining the notion of sustainability and green architecture in the design of residential buildings due to a lack of understanding about the role that sustainable design methods play in order to prevent detrimental effects on the environment and society. The researcher relies on the case-study methodology. The paper focuses on the sustainable features and new designs used in three case studies of green building in Dubai, China, and Indonesia. The findings demonstrated that these countries are aiming to promote the construction of green buildings, particularly in residential buildings, in order to attain sustainability as much as possible in the environmental, social and economic perspectives. These case studies prevail some important features used in the sustainable design of green buildings such like using renewable energy resources, water saving devices, waste management approaches, green transportation, natural lighting systems, and environmental building materials